Plato’s Critique of Writings/Orality and Theory of Principles - Erler, Michael (Peitho. Examina Antiqua, 2015)
The present paper is the first Polish translation of the following excerpts from the Author’s original and innovative book entitled Platon (Beck, München 2006): IV 4. a) Kritik der Schriftlichkeit; b) Hören des Richtiges, Verfehlen der Wahrheit: Platons Kritik der Mündlichkeit; IX 1. Schriftlicher Dialog und mündliches Prinziepiendenken; 2. Einheit und Vielheit: Ein Rekonstruktionsversuch; 3. Mündliche Lehre als Ergänzung des schriftlichen Dialogs. The book represents a new paradigm in research on Plato and the topics developed in it constitute a concise and coherent account of Plato’s critique of writing and orality as well as the related theory of principles. While these issues continue to be an area of scholarly debate, the authors groundbreaking proposals provide an invaluable point of reference for anyone truly interested in Plato’s philosophy. We are extremely grateful to the Author as well as the Publisher for their permission to publish a Polish translation of the aforementioned parts of this excellent book.